Effects of Alpha-Lactalbumin or Whey Protein Isolate on Muscle Damage, Muscle Pain, and Mood States Following Prolonged Strenuous Endurance Exercise - Qin, Lu; Wong, Stephen H. S.; Sun, Feng-Hua; Huang, Yu; Sheridan, Sinead; Sit, Cindy H. P. (Frontiers in Physiology, 2017)
This study compared the effect of alpha-lactalbumin and whey protein on muscle damage, muscle pain and mood states during short term recovery following strenuous prolonged exercise. In a two-stage crossover counterbalanced design, 12 endurance male runners were recruited (age: 30.4 ± 2.8 yr., height: 172.7 ± 5.6 cm, body mass: 66.7 ± 6.5 kg, V̇O2max: 58.0 ± 6.9 ml/kg-/min), ran for 90 minutes at 70% V̇O2max, and followed by a 4-h recovery. Two treatments (carbohydrate+alpha-lactalbumin, CA; carbohydrate+whey protein isolate, CW) were applied during the main trials. During the first 2-h of recovery, CHO was served at the rate of 0.66g/kg/h and PRO at 0.34g/kg/hevery 30 min. Creatine kinase (CK), interleukin-6 (IL-6), salivary cortisol, rating of muscle pain, pressure pain threshold (PPT) and mood states were evaluated before (Pre-ex), immediately (Post-ex0), 2h (Post-ex2h) and 4h (Post-ex4h) after exercise. 24h after exercise (Post-ex24h), CK and IL-6, muscle pain and PPT were evaluated. Compared with Pre-ex, Post-ex24h CK was higher in both trials of CA (398.16±41.37 vs. 184.77±22.68 IU/L, P=0.039) and CW (418.17±67.86 vs. 202.41±22.26 IU/L, P=0.037). IL-6 was also higher than Pre-ex at Post-ex0 and Post-ex2h in trials of CA (Post-ex0 vs. Pre-ex0: 7.87±0.74 vs. 1.69±0.23, P<0.01; Post-ex2h vs. Pre-ex0: 5.39±0.88 vs. 1.69±0.23, P=0.02) and CW (Post-ex0 vs. Pre-ex0: 8.63±1.06 vs. 1.59±0.19, P<0.01; Post-ex2h vs. Pre-ex0: 5.75±1.33 vs. 1.59±0.19, P<0.01). No difference was found in CK and IL-6 between two trials at all time points (all P>0.05). Compared with Pre-ex0, salivary cortisol was elevated at Post-ex0 in both trials (CA: 0.96±0.13 vs. 0.41±0.05 ng/ml, P<0.01; CW: 1.15±0.18 vs. 0.43±0.06 ng/ml, P<0.01) and was lower at Post-ex24h than Pre-ex in CA trial (0.17±0.02 vs. 0.41±0.05 ng/ml, P<0.01). Compared with CW, PPT was higher at Post-2h in CA trial (31.55±3.09 vs. 26.99±2.32 N/cm2, P<0.01). Compared with Post-ex0, feeling of fatigue was lower at Post-ex2h (P=0.014) and Post-ex4h (P<0.01) in CA, while it was lower at Post-ex4h (P=0.038) in CW. Compared with CW, feeling of fatigue was marginally lower in the CA trial at Post-ex2h (P=0.056). In conclusion, compared with the co-ingestion of CHO and whey PRO isolate, co-ingestion of CHO and alpha-lactalbumin reduced sensitivity